Determinación de ecuaciones alométricas para estimar biomasa y carbono en Pinus patula Schl. et Cham - Díaz-Franco, Rosalino; Acosta-Mireles, Miguel; Carrillo-Anzures, Fernando; Buendía-Rodríguez, Enrique; Flores-Ayala, Eulogio; Etchevers-Barra, Jorge D. (Instituto de Ecología, A.C., 2016)
In the community of “Mariano de Matamoros”, Tlaxco, Tlaxcala, 25 trees of Pinus patula Schl. et Cham., were selected and aboveground biomass and carbon contents were determined to fit the model Y=b*Xk, using diameter at breast height as an independent variable (X). A sample of each component (bole, branches and leaves) was obtained from each tree and both sample and total component fresh weight were determined in the field. The samples were taken to the laboratory to be dried and weighted so that, each tree’s biomass could be estimated, using the dry weight to fresh weight ratios of the samples. To determinate carbon contents for the different components, samples were taken from 25 trees and analyzed in the laboratory to obtain carbon content for leaves of 52,21%, branches 49,47%, bole 49,26% and an average concentration 50,31%. To estimate aboveground biomass the equation B = 0,0357 * DN2.6916 was fitted and to estimate carbon content the equation fitted was CC = 0,021 * DN 2.6451, with a coefficient of determination for both equations of 0,98.